Котик, котик, попляши!: стихи : [для дошкольного возраста] / Г. Р. Лагздынь - Лагздынь Гайда Рейнгольдовна (Репро, 2008)
Экземпляры: БС (20170911) / Инвентарный номер: РТШ51139 / Сис.шифр: Р2 / Авт.знак: Л 14 / ГРНТИ: 17.82.93 / ББК: 84(2)